A review of traditional uses and current applications of Cordia spp. (Boraginaceae) in the development of food and pharmaceutical products - Loor Constantine, Stephany; Pazmiño Viteri, Katherine; Vizuete, Karla; Debut, Alexis (Ethnobotany Research and Applications, 2023)
Background: The growing demand for natural polymers useful for food and drug production has prompted the search for new plant sources to replace synthetic polymers. Unlike synthetic polymers, natural ones have advantages such as low toxicity, biocompatibility, and non-toxicity to the environment. Among the plant sources investigated as biopolymers, we find gums and mucilage, which have achieved a remarkable position in the additive market due to their applications in the paper, cosmetic, food, and pharmaceutical industries, to name a few. The genus Cordia L. is traditionally known for its medicinal use, however, in recent years the fruit mucilage has been studied as a biopolymer. This review aims to compile and analyze the research conducted with species of the genus Cordia L., especially the ones that studied the mucilage of its fruits, including the methods applied to obtain, identify, and characterize it. Besides, talking about its application in new groundbreaking fields. Methods: Relevant information was selected from articles, books, theses, and patents published in databases such as Scopus, ScienceDirect, PubMed, Google Scholar, Google Patents, Patentscope, Patent Inspiration, and Espacenet. Results: The research data showed that the biopolymer obtained from fruit mucilage of the genus has attractive physical and chemical properties, and may be suitable for the design of drugs, nanoparticles, coatings, and food products. In addition, specific studies revealed the presence of some flavonoids and terpenes as active ingredients of the genus Cordia L., which are associated with their ancestral medicinal use. Conclusion: The possible use of mucilage of the genus Cordia L. is evidenced by its addition, substitution, or combination with other biopolymers to improve and design new products. Likewise, study alternatives are presented for countries where species of this genus are found and have not yet been considered for experimentation. Keywords: mucilage, gum, biomaterials, pharmaceutical industry, food industry, medicinal use.